2008
DOI: 10.1111/j.1442-9993.2007.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological interactions in the provision of habitat by urban development: whelks and engineering by oysters on artificial seawalls

Abstract: Increases in human population cause increased urbanization of most habitats, including the shoreline. This has many consequences for coastal environments, in particular the trend for artificial structures, such as seawalls, to replace natural habitats. Seawalls and natural shores support many of the common intertidal species, but others important on rocky shores are absent from or rare on many seawalls. The whelk Morula marginalba Blainville is an abundant and important predator on rocky shores of south-easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 71 publications
(95 reference statements)
0
26
0
Order By: Relevance
“…(Opisthobranchia). These species are typically absent from, or rare on, seawalls (Chapman 2003(Chapman , 2006Jackson et al 2008). Limpets of the species Siphonaria denticulata were extremely common (>7,000 adults counted).…”
Section: Abundances Of Mobile Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Opisthobranchia). These species are typically absent from, or rare on, seawalls (Chapman 2003(Chapman , 2006Jackson et al 2008). Limpets of the species Siphonaria denticulata were extremely common (>7,000 adults counted).…”
Section: Abundances Of Mobile Animalsmentioning
confidence: 99%
“…Interrelationships among species may also change. Jackson et al (2008) showed that biogenic habitat created by oysters increased densities of the whelk Morula marginalba on seawalls, although, on natural shores, whelks are not necessarily associated with oysters (Fairweather 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Common species on rocky shores may be found at unnatural densities or are absent from seawalls (Chapman 2003, Jackson et al 2008). The most abundant grazing animals on seawalls are limpets, which are major components of assemblages on natural intertidal shores, structuring algal and faunal assemblages (Branch 1981, Hawkins & Hartnoll 1983, Underwood et al 1983.…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic habitats the structural heterogeneity of sediments is related to a variety of factors such as variability of particle size (Brown, 2003) and availability of different food resources, as organic matter (Schwindt et al, 2001;Da Rocha et al, 2006). Variations in both particle size and food resource are often linked to presence of other organisms associated with these habitats (Jackson et al, 2008;Buschbaum et al, 2009). Habitat heterogeneity is a key factor enhancing the stability of communities, such as macroinvertebrates in environments exposed to great disturbances (Mykra et al, 2011).…”
Section: Introductionmentioning
confidence: 99%